2004
DOI: 10.1093/ageing/afh106
|View full text |Cite
|
Sign up to set email alerts
|

Fear-related avoidance of activities, falls and physical frailty. A prospective community-based cohort study

Abstract: fear-related avoidance of activities may have negative effects on physical abilities and may also be predictive for future falls. Avoidance of activities is therefore an important additional psychological variable in the development of physical frailty and falling in community-living elderly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

23
378
2
17

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 531 publications
(428 citation statements)
references
References 18 publications
23
378
2
17
Order By: Relevance
“…The prevalence of activity restriction of 57% of the elders who reported FOF corroborates several studies 6,11,12,29,30 , although lower prevalence were identified in this study 4,9,31,32 . These variations may be due to the use of different questionnaires for measuring activity restriction and to the differences in the characteristics of the evaluated population 29,31 .…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…The prevalence of activity restriction of 57% of the elders who reported FOF corroborates several studies 6,11,12,29,30 , although lower prevalence were identified in this study 4,9,31,32 . These variations may be due to the use of different questionnaires for measuring activity restriction and to the differences in the characteristics of the evaluated population 29,31 .…”
Section: Discussionsupporting
confidence: 91%
“…Gait is a necessary ability to perform the activities of daily living. Considering that mobility tasks are frequently restricted on elders 4 , it is possible that the longer time spent to walk certain distance by those who restricted activities due to fear of falling has happened due to the decline of physical capacities associated with physical inactivity and with social isolation 4,6,9 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations